Real-time pneumatic power maximization for oscillating water columns using a spatiotemporally aligned nonlinear model predictive control - Yan Huang; Xiaofu Ma; Weiwei Fan; Yongqiang Tu; Shaohui Yang; Jianyu Fan; Chenglong Li; Zhichang Du; Yuankui Wang (Ocean Engineering, 2026)

Preparation of a MOF-derived Mn-Ti catalyst and its simultaneous removal of NOx and toluene: Strong metal-support interaction and Lewis acid sites - Yongchao Zhong; Dan He; Qiangwei Lu; Lu Wang; Yunkuo Luo; Dongliang Zhang; Chaochao Li; Lin Li; Fengying Li; Xiang Tu; Chenglong Yu (Journal of Environmental Chemical Engineering, 2026)

A predictive efficiency maximization method based on active airflow control for an oscillating water column turbine - Yan Huang; Xiaofu Ma; Weixun Dong; Yongqiang Tu; Shaohui Yang; Jianyu Fan; Chenglong Li; Zhichang Du; Yuankui Wang (Ocean Engineering, 2026)

Proteomic Signatures of Dental Enamel Hypomineralization: Divergent Molecular Pathways in Coal-Burning vs. Drinking-Water Fluorosis - Na Yang; Jiabing Fan; Guobao Man; Wentai Wang; Jian Liao; Chenglong Tu (Biological Trace Element Research, 2025)

Stability Calculation and Roll Analysis for Oscillating Water Column Wave Energy Buoy - Songgen Zheng; Jiangyan Ke; Chenglong Li; Yongqiang Tu; Haoran Zhang; Shaohui Yang (Journal of Marine Science and Engineering, 2025)
This study presents a systematic analysis of the stability and roll characteristics of an Oscillating Water Column (OWC) wave energy buoy. By integrating theoretical derivation and AQWA simulation, the research identifies thirteen possible heeling states of OWC buoy, focusing on five representative states applicable to the current design. A novel segmented-integration model is proposed to compute the centre of buoyancy and righting moment for the hollow-annular OWC buoy, accurately capturing the evolution of static and dynamic stability across heel angles from 0° to 90°. Results show that the buoy has an initial metacentric height of 0.33 m, a maximum righting arm of 0.713 m, a limiting static heel angle of 77°, and a minimum capsizing moment of 22,887 N·m—all significantly exceeding regulatory requirements. The roll natural period ranges from 5.8 to 7.7 s, with a tuning factor above 1.3, effectively avoiding resonance with typical wave periods in the target sea area. The buoy demonstrates excellent dynamic stability and capsize resistance. This study fills a gap in OWC buoy stability analysis and provides a practical guidance for the safe design of wave energy devices.

Mercury isotope fractionation during natural travertine formation - Hongming Cai; Jiubin Chen; Zhongwei Wang; Wei Yuan; Zhengrong Wang; Hui Henry Teng; Xiangyu Zhu; Chenglong Tu; Congqiang Liu; Jacques Schott (Chemical Geology, 2025)

Regulating the Cu-Ce interaction of CuCeOx/SAPO-34 catalysts to achieve a wide reaction temperature window for the collaborative synergistic removal of NOx and toluene at low temperatures and reaction mechanisms - Rong Liu; Xuehui Jia; Lin Li; Fengying Li; Xiang Tu; Weicheng Xu; Hansun Fang; Danping Li; Hong Huang; Chenglong Yu (Journal of Hazardous Materials, 2025)

An Approach to Optimize the Efficiency of an Air Turbine of an Oscillating Water Column Based on Adaptive Model Predictive Control - Yan Huang; Weixun Dong; Jianyu Fan; Shaohui Yang; Zhichang Du; Yongqiang Tu; Chenglong Li; Beichen Lin (Journal of Marine Science and Engineering, 2025)
Wave energy, as a vast renewable resource, remains underutilized despite its high potential. The oscillating water column (OWC) is one of the most efficient way to harvest wave energy. Due to the randomness of ocean wave excitation, a control strategy is needed to keep the conversion efficiency of OWC at a certain level. In this paper, an adaptive model predictive control (AMPC) method is proposed to optimize the efficiency of the air turbine and improve the overall efficiency of the OWC. Experiments were conducted in a wave flume to obtain realistic wave data, which were fed into the AMPC model for simulations. Results indicate that AMPC-optimized turbine efficiency exhibits improved performance under regular wave conditions and significantly enhances efficiency within certain intervals under short-period irregular waves. However, as the wave period increases, optimization becomes less stable. Overall, the study concludes that the adaptive MPC model effectively optimizes turbine efficiency under most conditions, highlighting its potential for enhancing OWC performance.

Coexposure to fluoride and sulfur dioxide aggravates enamel mineralization disorders in mice by disrupting calcium homeostasis-mediated endoplasmic reticulum stress - Wentai Wang; Na Yang; Junlin Yang; Jiaojiao He; Guohui Bai; Chenglong Tu (Food and Chemical Toxicology, 2025)

Co-exposure to fluoride and sulfur dioxide induces abnormal enamel mineralization in rats via the FGF9-mediated MAPK signaling pathway - Ying Lv; Jin Yao; Yang Wang; Guohui Bai; Changhu Lin; Chenglong Tu (Environmental Research, 2024)

Effects of field-aging on the impact of biochar on herbicide fate and microbial community structure in the soil environment - Hongguang Cheng; Dan Xing; Gratien Twagirayezu; Shan Lin; Shangyi Gu; Chenglong Tu; Paul W. Hill; David R. Chadwick; Davey L. Jones (Chemosphere, 2024)

Heritable methylation marks associated with prostate cancer risk - James G. Dowty; Chenglong Yu; Mahnaz Hosseinpour; Jihoon Eric Joo; Ee Ming Wong; Tu Nguyen-Dumont; Joseph Rosenbluh; Graham G. Giles; Roger L. Milne; Robert J. MacInnis; Pierre-Antoine Dugué; Melissa C. Southey (Familial Cancer, 2023)
DNA methylation marks that are inherited from parents to offspring are known to play a role in cancer risk and could explain part of the familial risk for cancer. We therefore conducted a genome-wide search for heritable methylation marks associated with prostate cancer risk. Peripheral blood DNA methylation was measured for 133 of the 469 members of 25 multiple-case prostate cancer families, using the EPIC array. We used these families to systematically search the genome for methylation marks with Mendelian patterns of inheritance, then we tested the 1,000 most heritable marks for association with prostate cancer risk. After correcting for multiple testing, 41 heritable methylation marks were associated with prostate cancer risk. Separate analyses, based on 869 incident cases and 869 controls from a prospective cohort study, showed that 9 of these marks near the metastable epiallele VTRNA2-1 were also nominally associated with aggressive prostate cancer risk in the population.

Sulphur dioxide and fluoride co-exposure cause enamel damage by disrupting the Cl-/HCO3- ion transport - Junlin Yang; Tongtong Huang; Jianghui Zhang; Guohui Bai; Wentai Wang; Jie Yao; Zheng Chen; Chenglong Tu (Journal of Trace Elements in Medicine and Biology, 2023)

Sodium Fluoride and Sulfur Dioxide Derivatives Induce TGF-β1-Mediated NBCe1 Downregulation Causing Acid–Base Disorder of LS8 Cells - Ying Lv; Wentai Wang; Lili Yao; Jiaojiao He; Guohui Bai; Changhu Lin; Chenglong Tu (Biological Trace Element Research, 2023)

Determination of cadmium in Chinese pepper and its health implications based on bioaccessibility - Zelan Wang; Jie Yao; Chenglong Tu; Ting Yang; Dali Sun; Changhu Lin (Environmental Science and Pollution Research, 2022)

An Improved Bibliometric Analysis on Antibiotics in Soil Research - Chunli Zheng; Hongkai Liao; Chenglong Tu (Bulletin of Environmental Contamination and Toxicology, 2022)

Fluorine enrichment of vegetables and soil around an abandoned aluminium plant and its risk to human health - Lingling He; Chenglong Tu; Shouyang He; Jiulai Long; Ya Sun; Yan Sun; Changhu Lin (Environmental Geochemistry and Health, 2021)

Dynamics of soil organic carbon following land-use change: insights from stable C-isotope analysis in black soil of Northeast China - Chenglong Tu; Congqiang Liu; Timothy A. Quine; Matthew William Jones; Taoze Liu; Longbo Li; Wenjing Liu (Acta Geochimica, 2018)

Behavior of rare earth elements in granitic profiles, eastern Tibetan Plateau, China - Lifeng Cui; Zhiqi Zhao; Congqiang Liu; Sheng Xu; Taoze Liu; Chenglong Tu; Hu Ding (Acta Geochimica, 2017)

Soil organic carbon dynamics study bias deduced from isotopic fractionation in corn plant - Chenglong Tu; Congqiang Liu; Xiaohui Lu; Lifeng Cui; Jiayin Du (Acta Geochimica, 2017)

Ecosystem service delivery in Karst landscapes: anthropogenic perturbation and recovery - Timothy Quine; Dali Guo; Sophie M. Green; Chenglong Tu; Iain Hartley; Xinyu Zhang; Jennifer Dungait; Xuefa Wen; Zhaoliang Song; Hongyan Liu; Heather Buss; Timothy Barrows; et al. (Acta Geochimica, 2017)

Accumulation of trace elements in agricultural topsoil under different geological background - Chenglong Tu; Tengbing He; Congqiang Liu; Xiaohui Lu; Yunchao Lang (Plant and Soil, 2011)